High stakes testing and teacher access to professional opportunities: lessons from Indonesia. Issue 6 (1st November 2016) - Ashadi, Ashadi; Rice, Suzanne
Abstract: High-stakes testing regimes, in which schools are judged on their capacity to attain high student results in national tests, are becoming common in both developed and developing nations, including the United States, Britain and Australia. However, while there has been substantial investigation around the impact of high-stakes testing on curriculum and pedagogy, there has been very little research looking at the impact on teachers' professional opportunities. The current project used a case study approach to examine the impact a high-stakes national testing programme had on teachers' access to professional learning and their teaching allocations in four Indonesian public schools. It found that better qualified teachers were allocated to classes that would be sitting for the national examinations, and that these teachers were given much more access to professional learning opportunities than those teaching non-examined year levels. This in turn impacted negatively on the staff morale of less qualified teaching staff and potentially on their career trajectories. Findings suggest that school leaders should be wary of targeting better qualified and/or more experienced staff to year levels sitting for high-stakes tests, as this may lead to staff stratification within schools, limiting opportunities for staff to learn from one another and reducing the morale of less qualified and less experienced staff. They also add support to a substantial body of research that suggests policy-makers should be wary of the flow-on effects of using performance in high-stakes tests as the key means of judging school effectiveness.